Dietas suplementadas com óleos essenciais de cravo e alecrim e óleos protegidos (eugenol, timol e vanilina) sobre a qualidade da carne de novilhas terminada em confinamento - Monteschio, Jéssica de Oliveira (2017)
Forty animals (Heifers Nellore) were fed for seventy-three days with one of the following treatments: CON (without addition of essential oils); BLE - Protected blend of eugenol, thymol and vanillin (4 g / animal / day); ROS - Rosemary essential oil (4 g / animal / day); BCL - Protected blend - eugenol, thymol and vanillin (2 g / animal / day) + clove essential oil (2 g / animal / day) and BRC - Protected blend - eugenol, thymol and vanillin (1:33 g / animal / day) + rosemary essential oil (1:33 g / animal / day) + clove essential oil (1:33 g / animal / day). The pH (24 hours), temperature, drip loss, losses thawing, fat thickness, ribeye area and marbling were assessed in the Longissimus dorsi. In addition, we evaluated the effects of aging (one, seven, and 14 days) on the cooking loss of meat, texture, meat color, oxidation of lipids and antioxidant. The essential oils in the diet of Heifers had no effect (P> 0.05) on the pH of the meat, temperature, drip loss and thawing, marbling, ribeye area and fat thickness, but treatment with essential oils along with the protected mixture (BRC) had the lowest cooking loss, softness and intensity of red meat. The addition of essential oils diet decreased lipid oxidation in meat during maturation and resulted in higher values for lipid oxidation after 14 days of aging. The essential oil showed satisfactory results regardless of whether administered alone or with the protected mixture. The diets with essential oil and an active principle blend showed a better acceptance by consumer and the 7th aging day received higher scores (P <0.05). Also, the essential oil and the active principles or their mixture showed the highest scores for the meat visual evaluation, and the analyses in display (tray) showed similar results to random photos